ANTIECONOMY, ECONOMY CRISIS AND CRISIS OF ECONOMICS - Gylys, Povilas (Ekonomika, 2011)
The gist of this article is the idea that the orthodox theory of economic crisis unduly reduces its subject to business crisis and that it is the outcome of the narrowness and limitedness of the individualistic economic approach to the problem, employed mostly by neoliberals and libertarians. As individualists (the individualistic camp) explicitly or implicitly identify economy with market, their perception of an economic crisis is reduced to business crisis, crisis of the production of private goods. However, the concept of economy is broader than that of the market; thus, an economic crisis cannot be reduced to a business crisis. In addition, the theory of economic crisis could be enriched by the concept of anti-economy, which does not fit the individualistic economic paradigm. Therefore, a correction of the theory of economic crisis is needed, and this correction should be done in a holistic cognitive framework. Holism opens the possibility (which doesn’t automatically guarantee cognitive success) to look at the economic crisis through a wider lens, to perceive it as a whole. The shift from individualistic reductionism to holism allows us to see a correlation between cognitive crisis and crisis in real economy, and to introduce the concept of systemic crisis.